Influence of social, environmental and economic sustainable development goals (SDGs) over continuation of entrepreneurship and competitiveness - Shyla Del-Aguila-Arcentales; Aldo Alvarez-Risco; Micaela Jaramillo-Arévalo; Myreya De-la-Cruz-Diaz; María De las Mercedes Anderson-Seminario (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The Sustainable Development Goals (SDGs) were proposed in 2015 to promote worldwide improvements in human wellbeing. Governments have different levels of commitment to the SDGs, reflected in the SDG index, which shows the compliance of each country, detailing each score by SDG. The Global Entrepreneurship Monitor reports show the advances of global entrepreneurship in various countries, while the Global Competitiveness Report shows their competitiveness. This analysis was based on environmental, social, and economic outcomes of SDGs from the SDG index 2018. We also evaluated data from the Global Competitiveness Report 2018 and the Global Entrepreneurship Monitor report 2018. A partial least-squares structural-equation-modeling technical analysis was used. It was found that social SDGs (0.796) and environmental SDGs (0.196) had a positive influence on economic SDGs; also, economic SDGs had a positive influence on the continuation of entrepreneurship (0.590) and competitiveness (0.918). The model explained 34.8% of the continuation of entrepreneurship and 84.3% of that of competitiveness. The outcomes of the bootstrapping test were used to evaluate whether the path coefficients were significant. This information can help governments and organizations to recognize the impact of support and promote compliance with SDGs and the continuation of entrepreneurship and competitiveness. Moreover, this information provides the means to analyze the influence of open innovation in accomplishing the SDGs faster. The study's novelty is the use of the PLS-SEM technique to analyze these worldwide indicators.
Keywords: 650; competitiveness; continuation of entrepreneurship; entrepreneurs; SDG; SEM PLS; sustainable development goal